A comparative study of intraarticular versus subacromial corticosteroid injection in the treatment of frozen shoulder - Nagaraj, Preetham; Pattanshetty, Anusha S.; Mathews, Basil S. (International Journal of Research in Orthopaedics, 2024)
Background: Frozen shoulder or adhesive capsulitis, is a condition characterized by pain and restricted movement of the shoulder joint. Corticosteroid injections are commonly used to alleviate symptoms, but the optimal injection site remains debated. This comparative study aims to evaluate the efficacy of intraarticular versus subacromial corticosteroid injections in treating frozen shoulder. Methods: This prospective, randomized controlled study was conducted over 12 months, from November 2022 to October 2023, at Bangalore Medical College and Research Institute, Bangalore. A total of 60 patients diagnosed with adhesive capsulitis were enrolled and randomized into two groups: 30 patients in the intraarticular (IA) injection group and 30 patients in the subacromial (SA) injection group. Patients were randomly assigned to either the IA group or the SA group. The IA group received a 40 mg injection of Triamcinolone Hexacetonide with 4 ml of 2% lidocaine into the glenohumeral joint. SPSS (Version 25.0) was used for analysis. Results: Patients in the intraarticular group demonstrated significantly lower pain scores compared to those in the subacromial group at the 4th, 8th and 12th weeks (p<0.05). The intraarticular group consistently achieved higher Constant Shoulder Scores at 4, 8 and 12 weeks, suggesting a more effective recovery in shoulder function compared to the subacromial group. Conclusion: This study demonstrates that intraarticular corticosteroid injections are more effective than subacromial injections in treating patients with frozen shoulders, particularly in terms of pain relief and functional improvement.